Evaluating the E?ects of Topical Timolol 0.5% (Ophthalmic Solution) Over the Scalp in Case of Infantile Hemangioma - Niraj; Ranjan , Amit; Shandilya, Surabhi (Asian Journal of Medical Research, 2022)
Background: Infantile hemangioma (IH) is the most common tumour reported during infancy. These lesions are mostly proliferate during the first year of life after that involutions naturally happen within 7 years of age. We studied 15 patients out of whom seven completed all follow ups who were treated for IH on the scalp with topical application of 0.5% timolol maleate ophthalmic solution. The aims & objectives is to evaluate the effects and adverse effects of 0.5% topical timolol maleate solution in infantile hemangioma on the scalp. Subjects and Methods: Up to six month old children were included and treated with the drops of 0.5% timolol maleate ophthalmic solution twice daily on the lesions for 6 months. At the end of the study, patients were assessed about the acceptable outcome like, cosmetically acceptance, functional improvement, adverse reactions, especially alopecia. Results: Out of fifteen, seven children treated and followed up with timolol topical application. After six months treatment with 0.5% timolol maleate ophthalmic solution, the ratio of lesions which had complete improvement was 28.57% (2/7), substantial change in 14.28% (1/7), moderate change in 14.28% (1/7), fair change in 14.28% (1/7), minimal change in 14.28% (1/7), and only 1/7 cases (14.28%) did not change and the lesion increased in size. There were no adverse effects observed. Conclusion: Timolol maleate 0.5% ophthalmic solution has showed promising and safe results for the treatment of infantile hemangioma of scalp after 6 months of treatment without any significant side effect.